How Old Are the River Names of Europe? A Glottochronological Approach - Peust, Carsten (Linguistik Online, 2011)
The names of large rivers are among the diachronically most stable of all words. The present glottochronological study aims to quantify the lexical preservation rate of this set of words, more specifically of the names of the largest rivers of Europe. 210 river names are taken into consideration. Their preservation rate during the past 2000 years turns out to have been about 87%. Under the assumption that this observed rate can be extrapolated into the prehistoric periods, a statistical distribution of the name creation dates can be estimated. One conclusion is that 50% of the large modern rivers of Europe are likely to have received their present names prior to 8000 BC. This implies that the greater part of these names cannot be of Indo-European origin as has usually been assumed.